Integration of a problem-based multidisciplinary clinical cancer management course into undergraduate education - SARIKAYA, ÖZLEM (SPRINGER, 2004)
Background. Undergraduate cancer education programs usually involve diagnosis and treatment of various organs and tissues of the body that are invaded by this disease. Teaching organ system-based oncology by different disciplines causes a fragmented structure of knowledge with difficulty on reuniting the knowledge for the real patient. Methods. Along with the reorganization process of the curriculum, an integrated, problem-based multidisciplinary clinical cancer management course has been introduced to fifth-year students. The course has consisted of group studies, panel discussions, site visits to departments involved in diagnosis and treatment of cancer, and lecture tutorials enriched with interactive learning methods. Results and Conclusion. Overall assessment of the course has been encouraging in terms of a clinical approach for students to the cancer patient, and innovations for better learning have been implemented for the following year.
Keywords: MEDICAL-STUDENTS; KNOWLEDGE; PROGRAM